Allergic diseases in India – Prevalence, risk factors and current challenges. Issue 3 (24th October 2022) - Mahesh, Padukudru Anand; Moitra, Saibal; Mabalirajan, Ulaganathan; Garg, Mayank; Malamardi, Sowmya; Vedanthan, Pudupakkam K.; Christopher, Devasahayam Jesudas; Agrawal, Anurag; Krishna, Mamidipudi Thirumala
Abstract: Epidemiological studies have shown a rise in the prevalence of allergic diseases in India during the last two decades. However, recent evidence from the Global Asthma Network study has observed a decrease in allergic rhinitis, asthma and atopic dermatitis in children. Still, with a population over 1.3 billion, there is a huge burden of allergic rhinitis, asthma and atopic dermatitis, and this is compounded by an unmet demand for trained allergy specialists and poor health service framework. There is wide variation in the prevalence of allergic diseases between different geographical locations in India, and the reasons are unclear at present. This may at least in part be attributable to considerable heterogeneity in aero‐biology, weather, air pollution levels, cultural and religious factors, diet, socioeconomic strata and literacy. At present, factors enhancing risks and those protecting from development of atopy and allergic diseases have not been well delineated, although there is some evidence for the influence of genetic factors alongside cultural and environmental variables such as diet, exposure to tobacco smoke and air pollution and residence in urban areas. This narrative review provides an overview of data from India regarding epidemiology, risk factors and genetics and highlights gaps in evidence as well as areas for future research. Abstract : India has an estimated 37.5 million asthmatics with a large proportion having poorly controlled disease. The burden of atopic dermatitis and food allergy remains relatively low. There is heterogeneity in socio‐cultural, religious & behavioral practices, diet, climate and exposure to indoor and outdoor air pollution across the country, providing a great opportunity for research to investigate the interplay between genetic, epigenetic and environmental factors.